Cellulose nanocrystals (CNCs) as hard templates for preparing mesoporous zeolite Y assemblies with high catalytic activity. Issue 15 (16th July 2020) - Abdulridha, Samer; Jiang, Jiuxing; Xu, Shaojun; Zhou, Zhaoxia; Liang, He; Mao, Boyang; Zhou, Yangtao; Garforth, Arthur A.; Jiao, Yilai; Fan, Xiaolei
Abstract : Faujasite (FAU) Y zeolite assemblies with high mesoporosity ( S ext = 347 m 2 g −1 and V meso = 0.52 cm 3 g −1 ) were synthesised using sustainable and economic cellulose nanocrystals (CNCs) via a template-directed synthesis method. Abstract : Faujasite (FAU) Y zeolite assemblies with high mesoporosity ( S ext = 347 m 2 g −1 and V meso = 0.52 cm 3 g −1 ) were synthesised using sustainable and economic cellulose nanocrystals (CNCs) via a template-directed synthesis method, i.e. CNCs-Y. In comparison with the control zeolite catalysts of the conventional microporous Y and carbon nanotube templated Y (CNTs-Y) zeolites, the resulting CNCs-Y demonstrated superior performance in catalytic dealkylation with excellent activity and longevity, as well as the anti-coking ability thanks to the exceptional mesoporous features of CNCs-Y zeolites. Thereby, the method and relevant CNCs-Y mesoporous zeolites based on the sustainable CNCs presented here have significant implications for being developed further for improving the sustainability of relevant catalytic processes such as fluid catalytic cracking (FCC).